Pengaruh Faktor-Faktor Pembentuk Loyalitas Mahasiswa Universitas Terbuka - Ayuni, Devi; Mulyana, Andy (IPB University, 2015)
Currently the learning system based on Information and Communication Technology (ICT) has been growing. The Open University (UT) has been using e-learning in the provision of learning support services. Online tutorials (Tuton) is one form of e-learning provided UT. Since the registration period of 2013.1-2014.2, the number of courses offered in Tuton increased by 11% and participants also increased by 52%. Although Tuton has been growing rapidly, the total number of students has declined from the registration period of 2013.1 to 2015.1. Such a decrease can be justified as an indicator of lack of loyalty or retention of students. The main objective of this study is to test the relationship between the antecedents of loyalty, service quality, commitment, satisfaction, and reputation. The study population comes from four faculties and one graduate program. Nonprobability method of sampling with judgmental sampling technique is used in this study. The minimum required sample size is 200 respondents. Survey data collection is conducted by inviting respondents by email to fill out a questionnaire online in google site. Then the data were analyzed both descriptively and quantitatively using descriptive analysis and Structural Equation Modeling (SEM). Results of hypothesis testing showed that 6 of 7 hypothesis were accepted with significant results. These sixth hypothesis are1) the influence of the quality of services to satisfaction; 2) the effect of the reputation on the quality of services; 3) the effect of commitment to student satisfaction; 4) the effect of satisfaction on reputation; 5) the effect of satisfaction on loyalty; and 6) the effect of reputation on loyalty. As for the rejected hypothesis is the effect of reputation on commitment.Keywords : loyalty, quality of service, commitment, satisfaction, reputation